The Role of Commercial Banks in Industrial Development - Krzysztof Marecki; Agnieszka WOJCIK-CZERNIAWSKA (Communications of International Proceedings, 2022)
To a significant part, a country's ability to sustain development and growth is determined by several elements, one of which is finance. As a result, it is critical to remember that banking did not emerge as a result of chance, but rather as a result of Society's essential social and economic demands. The goal of this research is to investigate the function of commercial banks in industrial growth. The secondary data method has been used to find the role of commercial banks in industrial development. Savings Mobilization for Investment And growth, Savings Mobilization for Investment And growth, industry financing and trade liberalizing, etc are the main role that the commercial bank play in industrial development. It was discovered that several manufacturers believe commercial banks have not helped the growth of their companies, however, this should not be ascribed solely to commercial banks.
Keywords: Commercial Bank; Industrial development; technology; banking sector